2017
DOI: 10.1007/s10935-017-0494-3
|View full text |Cite
|
Sign up to set email alerts
|

Girls (and Boys) Just Want to Have Fun: A Mixed-Methods Examination of the Role of Gender in Youth Mentoring Relationship Duration and Quality

Abstract: This prospective, mixed-methods study examined the role of gender in youth mentoring relationship duration and quality. Participants were 67 gender-matched pairs of adult mentors and youth participating in community-based mentoring programs as well as the youths' guardians. Mentors and youth completed surveys and qualitative interviews at multiple time points. At baseline, male youth reported stronger relationships with their guardians. Analysis of the survey data from the 3-month follow-up revealed that male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
0
24
0
1
Order By: Relevance
“…Once all three interviews from a trifecta were coded, the coder produced a narrative summary (Maxwell & Miller, 2008;Way, 1998) integrating information from the coded interviews with the agency case notes. Narrative summaries were originally intended as a way to analyze data from a single reporter but have been adapted by Spencer and colleagues to examine the development of youth mentoring relationships, integrating data from multiple sources (e.g., Spencer at al., 2017;Spencer et al, 2018). Coders first explained the nature and development over time of the four main relationships examined in the interviews: mentor-youth, mentor-PG, mentor-MSS, PG-MSS.…”
Section: Discussionmentioning
confidence: 99%
“…Once all three interviews from a trifecta were coded, the coder produced a narrative summary (Maxwell & Miller, 2008;Way, 1998) integrating information from the coded interviews with the agency case notes. Narrative summaries were originally intended as a way to analyze data from a single reporter but have been adapted by Spencer and colleagues to examine the development of youth mentoring relationships, integrating data from multiple sources (e.g., Spencer at al., 2017;Spencer et al, 2018). Coders first explained the nature and development over time of the four main relationships examined in the interviews: mentor-youth, mentor-PG, mentor-MSS, PG-MSS.…”
Section: Discussionmentioning
confidence: 99%
“…Mentor retention is another significant challenge in the promotion of close and enduring formal youth mentoring relationships. Many adults enter into mentoring with high expectations for the experience and the difference they will be able to make in the life of a child (Spencer, 2007; Spencer, Basualdo-Delmonico, et al, 2017; Spencer, Drew, Walsh, & Kanchewa, 2017). The reality of mentoring, however, can be much more mundane and challenging, particularly in the early stages when mentors and youth may struggle to find common ground (Spencer, 2007).…”
Section: Yim and Mentor Recruitment And Retentionmentioning
confidence: 99%
“…Consequently, it may be that males feel more external pressure from members within their social network (e.g., peers, community, significant other) to become volunteers/mentors (Stukas et al, 2014). Another possibility stems from research about gender differences in expectations for mentoring, which has indicated that males tend to expect to have fun in their relationships and may enter into mentoring focused on this aspect of the relationship (Spencer et al, 2018). Agencies may want to consider the messaging in their recruitment efforts and/or tailor the messaging addressing how the volunteer opportunity may meet the motivations of prospective volunteers, particularly if they wish to increase their volunteer pool or target specific groups of volunteers (Dolnicar & Randle, 2007;Cornelis et al, 2013;Coursey et al, 2011).…”
Section: Discussionmentioning
confidence: 99%